Legal Protection for Advocates as Human Rights Defenders: An Analysis of Law No. 18 of 2003 on Advocates in Indonesia - Eka Putra Zakran; Achyar Zein; Mhd. Yadi Harahap (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2026)
The Indonesian Advocates’ Code of Ethics and Law Number 18 of 2003 concerning Advocates recognize advocates as members of an officium nobile and guarantee their professional independence in performing their duties as law enforcement officers and human rights defenders. However, the increasing incidence of intimidation, violence, and criminalization against advocates reveals a persistent gap between the legal protections guaranteed by law and their implementation in practice. Although advocates play a pivotal role in protecting human rights and ensuring access to justice, limited research has examined the effectiveness of Indonesia’s legal framework in safeguarding their professional independence through legal protection and the enforcement of the Code of Ethics. This study aims to evaluate the effectiveness of the existing legal framework in protecting advocates as human rights defenders, with particular emphasis on professional independence and the enforcement of the Indonesian Advocates’ Code of Ethics. The research adopts a normative legal method using statutory, conceptual, and case approaches. The analysis is based on Law Number 18 of 2003 concerning Advocates, the Indonesian Advocates’ Code of Ethics, relevant human rights instruments, and the case of the acid attack against advocate and human rights defender Andrie Yunus. The findings indicate that, despite formal legal guarantees of professional independence, the current framework remains ineffective due to weak institutional coordination, inconsistent law enforcement, and inadequate enforcement of the Code of Ethics. These shortcomings expose advocates to intimidation and violence, limiting their ability to perform their professional responsibilities independently. The study concludes that strengthening legal protection requires regulatory reform, more effective enforcement of the Code of Ethics, stronger institutional collaboration, and comprehensive protection mechanisms. These measures are essential to safeguarding advocates’ independence, improving access to justice, and reinforcing human rights protection in Indonesia.